Enhancing Budgeting Preparation Quality through Information Technology: A Casual Study on Motivation’s Moderating Effect - Adnans, Abdhy Aulia; Kasman, Andi; Siagian, Baihati; Zainuddin, Zhahirah Indrawati; Destrian, Ope (Fakultas Seni Rupa dan Desain ITB, 2025)
This study aims to determine and analyze the causal factors that contribute to the quality of budget preparation of the regional government budget (APBD). This causal study with motivation as a moderating variable employed 76 respondents from 34 sub-regional administrative units (SKPD) in Medan, Indonesia, using a saturated sample. Utilizingstructural equation modelling (SEM) with Smart-PLS, this study concludes that human resource competence and the use of information technology have a significant effect on the quality of APBD preparation. Motivation as a moderating variable does not exhibit a causal factor between the other two variables.